(untitled) (Journal of Bangladesh Institute of Planners, 2017)
Bangladesh, one of the largest countries in the world in terms of population, is characterized by rapid urbanization and growth. Alongside the remarkable rate of urban growth (in terms of population and GDP), the urban area in Bangladesh has been seen to expand horizontally, which is popularly termed as urban sprawl. Urban sprawl is the expansion of the geographic extent of cities and towns, resulting from factors including population growth and migration which have led to overcrowding, traffic congestion, added pressure on urban utilities like gas and water, larger informal sector, and unplanned slums and squatter settlements. This study explores the causes and consequences of urban sprawl and further identifies that the number of urban households, literacy rates and urban poverty relate positively to urban sprawl in Bangladesh using Census data from 1981-2011. Finally, this study identifies that urban population and population density are significant factors in explaining urban sprawl at the regional level in Chittagong, Dhaka, Khulna and Barisal divisions using a panel approach. While coefficients for urban population and literacy are positive, the sign of population density is negative, implying vertical expansion or economizing of land space in certain parts of the cities. As the availability of data remains a major drawback in the analysis of this urban problem, the approach is novel and presents further scope. It is expected that the interpretation from this research will add value to urban planners and decision makers, for policy decisions. JBIP, Vol. 10, 2017 (Printed in December 2019), pp. 15-23